Doped and coated composite sodium battery positive electrode material as well as preparation method and application thereof
By doping metal elements into the core of the sodium electropositive electrode material and coating the surface of the sodium ferro pyrophosphate material, the problem of poor circulation performance of the existing sodium electropositive electrode material is solved, and the structural stability and cyclic performance are improved, which is suitable for applications in the energy storage field.
Patent Information
- Application Number
- CN202411906236.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-28
AI Technical Summary
At present, the sodium-electric layered oxide positive electrode material has poor circulation performance, high raw material cost, low specific capacity and poor rate performance of polyanionic materials, resulting in poor overall electrical performance and cannot meet the application in the energy storage field.
Doped coated composite sodium electropositive electrode material is used to improve structural stability by doping metal elements in the core, and coat the core surface with high stability sodium phosphate phosphate material to avoid direct contact with the electrolyte and improve circulation performance.
It significantly improves the structural stability and cyclic performance of the sodium electropositive electrode material, maintains the cycle life of the core and shell, prevents HF erosion, and improves the overall electrical performance of the battery.
Smart Images

Figure CN119725455A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries and relates to a doped and coated composite sodium positive electrode material and a preparation method and application thereof. Background Art
[0002] Compared with lead-acid batteries, lithium-ion batteries have the advantages of high energy density, environmental friendliness and good cycle stability, making them a mature secondary battery technology that has been widely used in electric vehicles and electronic products. However, the high cost limits the practical application of lithium-ion batteries in large-scale energy storage systems.
[0003] The working principle of sodium-ion batteries is similar to that of lithium-ion batteries. Because sodium resources are abundant in the earth's crust, their inherent cost advantages make them an ideal alternative for large-scale energy storage applications. At present, there are three types of sodium-ion battery positive electrode materials that are widely developed and applied, including transition metal layered oxides, Prussian blue and polyanion materials. Among them, Prussian blue materials have not yet been commercialized on a large scale due to the problem of crystal water, while transition metal layered oxide materials have the advantage of high energy density, and polyanion materials have the advantage of good cycle stability, which makes these two types of materials have certain practical applications in the field of energy storage.
[0004] However, although the current sodium layered oxide cathode materials have good gram capacity, their cycle performance is poor and the cost of raw materials is high; although polyanion materials have the advantages of good cycle performance and low cost, their material specific capacity is low and the rate performance is poor. As a result, the overall electrical performance of the sodium ion battery made from them is not ideal and cannot meet its application in the field of energy storage.
[0005] Based on the above research, it is necessary to provide a sodium battery positive electrode material, which has a high capacity and excellent cycle performance. Summary of the invention
[0006] The object of the present invention is to provide a doped coated composite sodium positive electrode material and a preparation method and application thereof. The doped coated composite sodium positive electrode material can improve the structural stability of the sodium positive electrode material by doping in the core, and on the other hand, by coating the surface of the core with a sodium iron phosphate pyrophosphate material with high stability, it can avoid direct contact between the core and the electrolyte, thereby improving the cycle performance of the sodium positive electrode material.
[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a doped coated composite sodium positive electrode material, wherein the doped coated composite sodium positive electrode material comprises a core and a coating layer on the surface of the core;
[0009] The general chemical formula of the core is Na b Ni x Fe y Mn z M j O2, wherein M includes a doping metal element, x+y+z+j=1, 0.2≤x≤0.6, 0.2≤y≤0.5, 0.2≤z≤0.5, 0<j≤0.2, 0.8≤b≤1.2;
[0010] The coating layer includes sodium iron phosphate pyrophosphate material;
[0011] The raw materials for preparing the doped coated composite sodium positive electrode material include a core, a sodium iron phosphate pyrophosphate precursor material and a sodium source.
[0012] The doped coated composite sodium positive electrode material of the present invention is doped in the core, which can improve the structural stability of the core layered oxide material and maintain the matching of the core and shell cycle life of the doped coated composite sodium positive electrode material; the surface of the core is coated with a sodium iron phosphate pyrophosphate polyanion positive electrode material with excellent stability, and the coating of the surface sodium iron phosphate pyrophosphate material avoids direct contact between the core and the electrolyte, prevents HF from corroding the internal oxide of the particles, maintains the integrity of the core structure, and improves the stability and cycle performance of the sodium positive electrode material.
[0013] In addition, the present invention adopts an in-situ coating method to coat the sodium iron phosphate pyrophosphate material, and adopts an inner core, a sodium iron phosphate pyrophosphate precursor material and a sodium source for coating, so that the sodium iron phosphate pyrophosphate precursor material can be evenly distributed on the surface of the inner core, thereby obtaining a material with a uniform coating layer. If the finished sodium iron phosphate pyrophosphate material is prepared by a conventional solid-phase sintering method, the coating layer formed is generally a particle point coating, and a uniform coating film layer cannot be obtained. However, the present invention adopts the sodium iron phosphate pyrophosphate precursor material for in-situ coating, and can obtain a uniformly distributed coating layer.
[0014] Preferably, the sodium iron phosphate pyrophosphate precursor material is an amorphous nanomaterial.
[0015] The sodium iron phosphate pyrophosphate precursor material of the present invention is an amorphous nano material with low hardness and easy to break, which is conducive to the uniform coating of the sodium iron phosphate pyrophosphate precursor material.
[0016] Preferably, the chemical formula of the sodium iron phosphate pyrophosphate material is Na4Fe m P4O 12+m , wherein 2.5≤m≤3, for example, it can be 2.5, 2.6, 2.7, 2.8, 2.9 or 3, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0017] Preferably, the coating layer further comprises a carbon source.
[0018] Preferably, the carbon source comprises carbon nanotubes.
[0019] The sodium iron phosphate pyrophosphate material of the present invention is also doped with carbon nanotubes, which is beneficial to improving the conductivity of the doped and coated composite sodium positive electrode material, thereby improving the electrical performance of the material.
[0020] Preferably, the M includes Cu.
[0021] The core of the present invention is preferably doped with Cu, which is beneficial to improving the stability of the core structure.
[0022] Preferably, the mass ratio of the coating layer to the core is (0.5-2.0):1, for example, 0.5:1, 1:1, 1.5:1 or 2:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0023] The mass ratio of the coating layer to the core of the present invention is within a specific range, which is beneficial to matching the structural stability of the core and the coating layer, thereby ensuring the overall cyclic stability of the material.
[0024] In a second aspect, the present invention provides a method for preparing the doped coated composite sodium positive electrode material as described in the first aspect, the preparation method comprising the following steps:
[0025] The core, the sodium iron phosphate pyrophosphate precursor material and the sodium source are mixed and sintered to obtain the doped and coated composite sodium positive electrode material.
[0026] The present invention first prepares a doped layered oxide positive electrode material core with uniform element distribution, then coats a layer of nano-phosphate sodium iron pyrophosphate precursor material on its surface, and finally obtains a doped coated composite sodium positive electrode material with excellent performance through sintering.
[0027] Preferably, the method for preparing the sodium iron phosphate pyrophosphate precursor material comprises the following steps:
[0028] A ferrous source, a phosphorus source, a pyrophosphate source, a sodium source and a solvent are mixed to obtain a mixed solution, wherein the mixed solution is acidic, and then an oxidant is introduced into the mixed solution to perform a precipitation reaction to obtain the sodium iron pyrophosphate precursor material.
[0029] The method of the present invention is used to prepare the sodium iron phosphate pyrophosphate precursor material, and a nano sodium iron phosphate pyrophosphate precursor material with extremely fine primary particle size, low hardness, easy breakage and amorphous can be obtained, so that when the inner core, the sodium iron phosphate pyrophosphate precursor material and the sodium source are mixed, the primary particles of the sodium iron phosphate pyrophosphate precursor material are fine, amorphous and easy to break, and can be evenly coated on the surface of the inner core, thereby finally forming a uniform coating layer.
[0030] The present invention first mixes the raw materials to obtain an acidic mixed solution, then adds an oxidant to carry out a precipitation reaction under acidic conditions, and the reaction principle is that the gradually added oxidant such as hydrogen peroxide slowly oxidizes divalent iron into trivalent iron, and the trivalent iron quickly reacts with phosphate and pyrophosphate at this pH to form an insoluble precipitate; compared with the method of adding an alkaline precipitant such as ammonia water to an iron salt, a phosphorus source and a sodium source solution for precipitation to prepare a sodium iron phosphate pyrophosphate precursor, the precipitate prepared by the method has a lower content of iron hydroxide, and the obtained finished product has a better phase purity.
[0031] Preferably, the molar ratio of the oxidant to the ferrous source is (0.6-1.2):1, for example, 0.6:1, 0.8:1, 1.0:1 or 1.2:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0032] Preferably, the oxidant comprises hydrogen peroxide.
[0033] Preferably, the molar ratio of iron to phosphorus in the mixed solution is (0.625-0.750):1, for example, it can be 0.625:1, 0.65:1, 0.70:1 or 0.75:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0034] Preferably, the pH of the mixed solution is 1 to 3, for example, 1, 2 or 3, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0035] Preferably, the oxidant is introduced for 30 min to 100 min, for example, 30 min, 50 min, 70 min, 90 min or 100 min, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0036] Preferably, the precipitation reaction temperature is 30°C to 60°C, for example, 30°C, 40°C, 50°C or 60°C, and the pH is 1.5 to 2.0, for example, 1.5, 1.6, 1.7, 1.8 or 2.0, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0037] When the sodium iron phosphate pyrophosphate precursor material is prepared by the present invention, conditions such as reaction temperature, reaction pH and introduction time of the oxidant will affect the size and hardness of the primary particles of the sodium iron phosphate pyrophosphate precursor material. The present invention is preferably within the above-mentioned characteristic range, which is conducive to obtaining an amorphous, low hardness, and easily breakable sodium iron phosphate pyrophosphate precursor nanomaterial.
[0038] Preferably, the ferrous source comprises ferrous sulfate.
[0039] Preferably, the phosphorus source comprises phosphoric acid.
[0040] Preferably, the pyrophosphate source comprises sodium pyrophosphate.
[0041] Preferably, the sodium source comprises sodium hydroxide.
[0042] Preferably, the method for preparing the core comprises the following steps:
[0043] Passing a metal salt solution, a precipitant solution and a complexing agent solution into the base solution to perform a coprecipitation reaction to obtain a precursor material, wherein the mixed metal salt solution includes a formula amount of nickel ions, iron ions, manganese ions and M ions;
[0044] The precursor material and the sodium source are mixed and calcined according to the formula amount to obtain the core.
[0045] Preferably, the coprecipitation reaction is carried out under a protective atmosphere.
[0046] Preferably, the coprecipitation reaction temperature is 20°C to 70°C, for example, 20°C, 40°C, 60°C or 70°C, and the pH value is 8 to 12, for example, 8, 9, 10, 11 or 12, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0047] Preferably, the calcination temperature is 800°C to 1400°C, for example, 800°C, 1000°C, 1200°C or 1400°C, and the calcination time is 10h to 25h, for example, 10h, 15h, 20h or 25h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0048] Preferably, the calcination is carried out in an oxygen atmosphere.
[0049] Preferably, when the core, the sodium iron phosphate pyrophosphate precursor material and the sodium source are mixed, a carbon source is also added.
[0050] Preferably, the mass ratio of the core, sodium iron phosphate pyrophosphate precursor material, sodium source and carbon source is (25-55):(25-55):(15-25):1, for example, it can be 25:55:15:1, 50:45:25:1 or 25:25:20:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0051] Preferably, the sintering is performed in a protective gas.
[0052] Preferably, the sintering temperature is 600°C to 800°C, for example, 600°C, 700°C or 800°C, and the sintering time is 6h to 12h, for example, 6h, 8h, 10h or 12h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0053] In a third aspect, the present invention provides a sodium ion battery, which comprises the doped and coated composite sodium positive electrode material as described in the first aspect.
[0054] Compared with the prior art, the present invention has the following beneficial effects:
[0055] (1) The core of the doped coated composite sodium positive electrode material of the present invention is uniformly doped with M elements, such as an appropriate amount of copper element, which can improve the structural stability of the core layered oxide material and maintain the matching of the cycle life of the core and shell of the composite positive electrode material.
[0056] (2) The present invention coats the surface of the inner core with a sodium ferric phosphate pyrophosphate polyanion positive electrode material with excellent stability, thereby avoiding direct contact between the inner core and the electrolyte, preventing HF from corroding the oxide inside the particles, and maintaining the integrity of the inner core layered oxide structure; in addition, the sodium ferric phosphate pyrophosphate material is doped with carbon nanotubes, which is beneficial to improving the conductivity of the positive electrode material particles, thereby improving the electrical properties of the material.
[0057] (3) The coating layer of the present invention is prepared by using a sodium iron phosphate pyrophosphate precursor material, wherein the sodium iron phosphate pyrophosphate precursor material is prepared by wet precipitation, and the obtained precursor has an extremely fine primary particle size and a relatively low hardness, which is conducive to uniform coating on the surface of the inner core during the coating mixing process. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] Figure 1 This is a SEM image of the sodium iron pyrophosphate precursor material described in Example 1 of the present invention;
[0059] Figure 2 This is a SEM image of the nickel-iron-manganese-copper layered oxide precursor material described in Example 1 of the present invention;
[0060] Figure 3This is a SEM image of the doped and coated composite sodium positive electrode material described in Example 1 of the present invention. DETAILED DESCRIPTION
[0061] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0062] Example 1
[0063] This embodiment provides a doped coated composite sodium positive electrode material, the doped coated composite sodium positive electrode material comprises a core and a coating layer on the surface of the core, the core is NaNi 0.33 Fe 0.33 Mn 0.33 M 0.01 O2, the coating layer includes carbon nanotubes and sodium iron pyrophosphate material, the chemical formula of the sodium iron pyrophosphate material is Na4Fe 2.8 P4O 14.8 ;
[0064] The mass ratio of the coating layer to the core is 1:1;
[0065] The preparation method of the doped coated composite sodium positive electrode material comprises the following steps:
[0066] (1) dissolving 0.7 mol of ferrous sulfate, 0.4 mol of phosphoric acid, 0.3 mol of sodium pyrophosphate, and 0.5 mol of sodium hydroxide in water to prepare a mixed solution, wherein the iron-phosphorus ratio in the mixed solution is 0.70 and the pH is 2.0; then injecting 45 mL of 30% hydrogen peroxide into the mixed solution for precipitation reaction, the injection time is 50 min, the reaction temperature is 50° C., and the precipitation reaction is carried out under the condition of maintaining the pH value at 1.6 to 2.1, thereby obtaining a sodium iron pyrophosphate precursor material;
[0067] (2) nickel sulfate, iron sulfate, manganese chloride, and copper chloride are mixed in water at a metal molar ratio of 0.33:0.33:0.33:0.01 to obtain a mixed metal salt solution, and the mixed metal salt solution, sodium hydroxide solution, and ammonia water are added to the bottom liquid in parallel, and a coprecipitation reaction is carried out at a reaction temperature of 50° C. under nitrogen protection, and the pH value of the reaction system is controlled between 11.0 and 11.2. The reaction is carried out for 50 hours, and the average particle size reaches 5.0 μm, and the reaction is stopped. After washing and drying, a nickel-iron-manganese-copper layered oxide precursor material is obtained;
[0068] (3) high temperature sintering: mixing the nickel-iron-manganese-copper layered oxide precursor material obtained in step (2) with sodium carbonate, sintering at 1000° C. for 12 h in a tube furnace under oxygen flow, and grinding and screening to obtain a sodium-electrolyte layered oxide core material;
[0069] (4) The above-mentioned sodium electrode layered oxide core material, sodium iron phosphate pyrophosphate precursor material, sodium carbonate and carbon nanotubes are mixed in a mass ratio of 50:50:20:1 and ball milled for coating treatment. Then, the mixture is sintered at 700°C for 8h in a nitrogen atmosphere to obtain the doped and coated composite sodium electrode positive electrode material.
[0070] The SEM image of the sodium iron phosphate pyrophosphate precursor material prepared in this example is as follows: Figure 1 As shown, from Figure 1 It can be seen that the primary particle size of the sodium iron phosphate pyrophosphate precursor material is small and has an amorphous structure; the SEM image of the nickel iron manganese copper layered oxide precursor material prepared in this embodiment is as follows Figure 2 As shown; the SEM image of the doped coated composite sodium positive electrode material prepared in this embodiment is as shown Figure 3 shown.
[0071] Example 2
[0072] This embodiment provides a doped coated composite sodium positive electrode material, the doped coated composite sodium positive electrode material comprises a core and a coating layer on the surface of the core, the core is NaNi 0.3 Fe 0.4 Mn 0.28 M 0.02 O2, the coating layer includes carbon nanotubes and sodium iron pyrophosphate material, the chemical formula of the sodium iron pyrophosphate material is Na4Fe 2.9 P4O 14.9 ;
[0073] The mass ratio of the coating layer to the core is 1:1;
[0074] The preparation method of the doped coated composite sodium positive electrode material comprises the following steps:
[0075] (1) 0.72 mol of ferrous sulfate, 0.4 mol of phosphoric acid, 0.3 mol of sodium pyrophosphate, 0.6 mol of sodium hydroxide and water are prepared to obtain a mixed solution, wherein the iron-phosphorus ratio in the mixed solution is 0.72 and the pH is 2.2. Then 50 ml of 30% hydrogen peroxide is injected into the mixed solution for precipitation reaction, the injection time is 60 min, the reaction temperature is 55° C., and the precipitation reaction is carried out under the condition of maintaining the pH value at 1.7 to 2.3, thereby obtaining a sodium iron pyrophosphate precursor material;
[0076] (2) Nickel chloride, ferric chloride, manganese chloride and copper chloride are mixed with water at a metal molar ratio of 0.30:0.40:0.28:0.02 to obtain a mixed metal salt solution, and the mixed metal salt solution, sodium hydroxide solution and ammonia water are added to the bottom liquid in parallel. Under nitrogen protection, a coprecipitation reaction is carried out at a reaction temperature of 55°C, and the pH value of the reaction system is controlled between 10.6 and 10.8. The reaction is carried out for 80 hours, and the average particle size reaches 7.0 μm. The reaction is stopped, and the nickel-iron-manganese-copper layered oxide precursor material is obtained after washing and drying;
[0077] (3) high temperature sintering: the nickel-iron-manganese-copper layered oxide precursor material described in step (2) is fully mixed with sodium carbonate, and sintered in a tubular furnace under oxygen flow at 1100° C. for 10 h, and then ground and sieved to obtain a sodium-electrolyte layered oxide core material;
[0078] (4) The sodium battery layered oxide core material, sodium iron phosphate pyrophosphate precursor material, sodium carbonate and carbon nanotubes are mixed in a mass ratio of 50:50:20:1 and ball-milled for coating treatment; finally, the coated material is sintered at 750°C for 7 hours under a nitrogen atmosphere to obtain the doped coated composite sodium battery positive electrode material.
[0079] Example 3
[0080] This embodiment provides a doped coated composite sodium positive electrode material, the doped coated composite sodium positive electrode material comprises a core and a coating layer on the surface of the core, the core is NaNi 0.33 Fe 0.33 Mn 0.33 M 0.01 O2, the coating layer includes carbon nanotubes and sodium iron pyrophosphate material, the chemical formula of the sodium iron pyrophosphate material is Na4Fe 2.82 P4O 14.82 ;
[0081] The mass ratio of the coating layer to the core is 0.5:1;
[0082] The preparation method of the doped coated composite sodium positive electrode material comprises the following steps:
[0083] (1) 0.7 mol of ferrous sulfate, 0.4 mol of phosphoric acid, 0.3 mol of sodium pyrophosphate, and 0.5 mol of sodium hydroxide are dissolved in water to prepare a mixed solution, wherein the iron-phosphorus ratio in the mixed solution is 0.70 and the pH is 2.0; then 45 mL of 30% hydrogen peroxide is injected into the mixed solution for precipitation reaction, the injection time is 50 min, the reaction temperature is 60° C., and the precipitation reaction is carried out under the condition of maintaining the pH value at 1.6 to 2.1, thereby obtaining a sodium iron pyrophosphate precursor material;
[0084] (2) nickel sulfate, iron sulfate, manganese chloride, and copper chloride are mixed in water at a metal molar ratio of 0.33:0.33:0.33:0.01 to obtain a mixed metal salt solution, and the mixed metal salt solution, sodium hydroxide solution, and ammonia water are added to the bottom liquid in parallel, and a coprecipitation reaction is carried out at a reaction temperature of 70° C. under nitrogen protection, and the pH value of the reaction system is controlled between 11.0 and 11.2. The reaction is carried out for 50 hours, and the average particle size reaches 5.0 μm, and the reaction is stopped. After washing and drying, a nickel-iron-manganese-copper layered oxide precursor material is obtained;
[0085] (3) high temperature sintering: mixing the nickel-iron-manganese-copper layered oxide precursor material obtained in step (2) with sodium carbonate, sintering at 1400° C. for 10 h in a tube furnace under oxygen flow, and obtaining a sodium-electrolyte layered oxide core material after grinding and screening;
[0086] (4) The above-mentioned sodium electrode layered oxide core material, sodium iron phosphate pyrophosphate precursor material, sodium carbonate and carbon nanotubes are mixed in a mass ratio of 50:25:15:1 and ball-milled for coating treatment. Then, the mixture is sintered at 600° C. for 12 h in a nitrogen atmosphere to obtain the doped and coated composite sodium electrode positive electrode material.
[0087] Example 4
[0088] This embodiment provides a doped coated composite sodium positive electrode material, the doped coated composite sodium positive electrode material comprises a core and a coating layer on the surface of the core, the core is NaNi 0.33 Fe 0.33 Mn 0.33 M 0.01 O2, the coating layer includes carbon nanotubes and sodium iron pyrophosphate material, the chemical formula of the sodium iron pyrophosphate material is Na4Fe 2.78 P4O 14.78 ;
[0089] The mass ratio of the coating layer to the core is 2:1;
[0090] The preparation method of the doped coated composite sodium positive electrode material comprises the following steps:
[0091] (1) dissolving 0.7 mol of ferrous sulfate, 0.4 mol of phosphoric acid, 0.3 mol of sodium pyrophosphate, and 0.5 mol of sodium hydroxide in water to prepare a mixed solution, wherein the iron-phosphorus ratio in the mixed solution is 0.70 and the pH is 2.0; then injecting 55 mL of 30% hydrogen peroxide into the mixed solution for precipitation reaction, the injection time is 70 min, the reaction temperature is 40° C., and the precipitation reaction is carried out under the condition of maintaining the pH value at 1.5 to 2.0, thereby obtaining a sodium iron pyrophosphate precursor material;
[0092] (2) nickel sulfate, iron sulfate, manganese chloride, and copper chloride are mixed in water at a metal molar ratio of 0.33:0.33:0.33:0.01 to obtain a mixed metal salt solution, and the mixed metal salt solution, sodium hydroxide solution, and ammonia water are added to the bottom liquid in parallel, and a coprecipitation reaction is carried out at a reaction temperature of 70° C. under nitrogen protection, and the pH value of the reaction system is controlled between 11.0 and 11.2. The reaction is carried out for 50 hours, and the average particle size reaches 5.0 μm, and the reaction is stopped. After washing and drying, a nickel-iron-manganese-copper layered oxide precursor material is obtained;
[0093] (3) high temperature sintering: mixing the nickel-iron-manganese-copper layered oxide precursor material obtained in step (2) with sodium carbonate, sintering at 800° C. for 25 h in a tube furnace under oxygen flow, and obtaining a sodium-electrolyte layered oxide core material after grinding and screening;
[0094] (4) The above-mentioned sodium electrode layered oxide core material, sodium iron phosphate pyrophosphate precursor material, sodium carbonate and carbon nanotubes in a mass ratio of 25:50:25:1 are mixed and ball-milled for coating treatment, and then sintered at 800° C. for 6 h in a nitrogen atmosphere to obtain the doped and coated composite sodium electrode positive electrode material.
[0095] Example 5
[0096] The present embodiment provides a doped coated composite sodium positive electrode material. The doped coated composite sodium positive electrode material is the same as Example 1 except that in its preparation method, the preparation method of the sodium iron pyrophosphate precursor material is changed to make the adaptability of the obtained doped coated composite sodium positive electrode material change.
[0097] The preparation method of the sodium iron phosphate pyrophosphate precursor material described in this embodiment includes: taking 0.15 mol of ferric nitrate nonahydrate and 0.20 mol of sodium dihydrogen phosphate and dissolving them in 50 mL of deionized water to form a solution A, taking 50 mL of ammonia water with a mass fraction of 28%, dripping it dropwise into the solution A to start precipitation, and after the reaction is complete, heat treating at 80° C. to obtain the sodium iron phosphate pyrophosphate precursor material.
[0098] Example 6
[0099] This embodiment provides a doped and coated composite sodium positive electrode material. The doped and coated composite sodium positive electrode material is the same as Example 1 except that no carbon nanotubes are added in the preparation method, so that the coating layer of the obtained doped and coated composite sodium positive electrode material does not contain carbon nanotubes.
[0100] Example 7
[0101] The present embodiment provides a doped coated composite sodium positive electrode material. The doped coated composite sodium positive electrode material is the same as that in Example 1 except that in the preparation method thereof, when preparing the sodium iron pyrophosphate precursor material in step (1), the pH value of the precipitation reaction is 1.2 to 1.4, so that the adaptability of the doped coated composite sodium positive electrode material changes.
[0102] Example 8
[0103] The present embodiment provides a doped coated composite sodium positive electrode material. The doped coated composite sodium positive electrode material is the same as that in Example 1 except that in the preparation method thereof, when preparing the sodium iron pyrophosphate precursor material in step (1), the pH value of the precipitation reaction is 2.6 to 2.8, so that the adaptability of the doped coated composite sodium positive electrode material changes.
[0104] Comparative Example 1
[0105] This comparative example provides a sodium positive electrode material, which is the same as Example 1 except that in the preparation method thereof, the mixed metal salt solution in step (2) does not contain copper ions, so that the core does not contain Cu.
[0106] Comparative Example 2
[0107] This comparative example provides a sodium positive electrode material, which is the same as Example 1 except that in its preparation method, step (1) is not performed, and in step (4), the sodium layered oxide core material and the sodium iron phosphate pyrophosphate positive electrode material prepared by the solid phase method are subjected to subsequent steps in a mass ratio of 1:1 to make the adaptability of the obtained sodium positive electrode material change.
[0108] Comparative Example 3
[0109] This comparative example provides a sodium positive electrode material. The sodium positive electrode material is the same as Example 1 except that in the preparation method thereof, the mixed metal salt solution in step (2) does not contain copper ions, step (1) is not performed, and in step (4), the sodium layered oxide core material and the sodium iron phosphate pyrophosphate positive electrode material prepared by a solid phase method are subjected to subsequent steps in a mass ratio of 1:1 to change the adaptability of the obtained sodium positive electrode material.
[0110] At 25°C, the sodium positive electrode materials obtained in the above examples and comparative examples were prepared into positive electrode sheets, and the metal sodium sheet was used as the negative electrode to assemble into CR2032 button batteries. Then, the discharge current density was 10 mA g in the voltage range of 1.5-4.0 V. -1 The electrochemical performance test was carried out under the following conditions. The test results of the capacity retention rate after 10,000 cycles are shown in Table 1 below:
[0111] Table 1
[0112]
[0113]
[0114] From Table 1 we can see that:
[0115] It can be seen from Example 1 and Comparative Examples 1-3 that the doped and coated composite sodium positive electrode material can significantly improve the cycle performance of the material by doping and coating. For example, the battery prepared in Example 1 has a capacity retention rate of more than 82% after 10,000 cycles, while that of Comparative Examples 1-3 is less than 72%. In addition, the present invention uses a core, a sodium iron phosphate pyrophosphate precursor material and a sodium source for coating. If the sodium iron phosphate pyrophosphate positive electrode material prepared by a conventional solid phase method is used for coating, uniform coating cannot be achieved. Therefore, even after coating, the cycle performance is lower than that of the present invention; It can be seen from Example 1 and Example 5 that It is known that the sodium iron phosphate pyrophosphate precursor material of the present invention is prepared by a specific method, and the primary particle size of the obtained material is relatively fine and easy to break. When mixed with materials such as the core, it can be evenly coated on the surface of the core, thereby significantly improving the cycle performance of the material; it can be known from Example 1 and Example 6 that the preferred coating layer of the present invention also includes carbon nanotubes, which is beneficial to improving the performance of the battery; it can be known from Example 1 and Examples 7-8 that changes in conditions during the preparation of the sodium iron phosphate pyrophosphate precursor material of the present invention will affect the morphology and hardness of the generated particles, thereby affecting the coating effect and the cycle performance of the battery.
[0116] In summary, the present invention provides a doped and coated composite sodium positive electrode material and a preparation method and application thereof. The doped and coated composite sodium positive electrode material can improve the structural stability of the sodium positive electrode material by doping in the core, and on the other hand, by coating the surface of the core with a sodium iron phosphate pyrophosphate material with high stability, it can avoid direct contact between the core and the electrolyte, thereby improving the cycle performance of the sodium positive electrode material.
[0117] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.
Claims
1. A doped and coated composite sodium positive electrode material, characterized in that: The doped coated composite sodium positive electrode material comprises a core and a coating layer on the surface of the core; The general chemical formula of the core is Na b Ni x Fe y Mn z M j O2, wherein M includes a doping metal element, x+y+z+j=1, 0.2≤x≤0.6, 0.2≤y≤0.5, 0.2≤z≤0.5, 0<j≤0.2, 0.8≤b≤1.2; The coating layer includes sodium iron phosphate pyrophosphate material; The raw materials for preparing the doped coated composite sodium positive electrode material include a core, a sodium iron phosphate pyrophosphate precursor material and a sodium source.
2. The doped and coated composite sodium positive electrode material according to claim 1, characterized in that: The sodium iron phosphate pyrophosphate precursor material is an amorphous nanomaterial; Preferably, the chemical formula of the sodium iron phosphate pyrophosphate material is Na4Fe m P4O 12+m , where 2.5≤m≤3.
3. The doped and coated composite sodium positive electrode material according to claim 1 or 2, characterized in that: The coating layer also includes a carbon source; Preferably, the carbon source comprises carbon nanotubes; Preferably, said M comprises Cu; Preferably, the mass ratio of the coating layer to the core is (0.5-2.0):
1.
4. A method for preparing a doped and coated composite sodium positive electrode material as claimed in any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: The core, the sodium iron phosphate pyrophosphate precursor material and the sodium source are mixed and sintered to obtain the doped and coated composite sodium positive electrode material.
5. The preparation method according to claim 4, characterized in that: The method for preparing the sodium iron phosphate pyrophosphate precursor material comprises the following steps: Mixing a ferrous source, a phosphorus source, a pyrophosphate source, a sodium source and a solvent to obtain a mixed solution, wherein the mixed solution is acidic, and then introducing an oxidant into the mixed solution for a precipitation reaction to obtain the sodium iron pyrophosphate precursor material; Preferably, the molar ratio of the oxidant to the ferrous source is (0.6-1.2):1; Preferably, the oxidant comprises hydrogen peroxide; Preferably, the molar ratio of iron to phosphorus in the mixed solution is (0.625-0.750):1; Preferably, the pH of the mixed solution is 1 to 3; Preferably, the oxidant is introduced for 30 to 100 minutes; Preferably, the precipitation reaction temperature is 30°C to 60°C, and the pH is 1.5 to 2.
0.
6. The preparation method according to claim 5, characterized in that: The ferrous source includes ferrous sulfate; Preferably, the phosphorus source comprises phosphoric acid; Preferably, the pyrophosphate source comprises sodium pyrophosphate; Preferably, the sodium source comprises sodium hydroxide.
7. The preparation method according to any one of claims 4 to 6, characterized in that: The method for preparing the core comprises the following steps: Passing a metal salt solution, a precipitant solution and a complexing agent solution into the base solution to perform a coprecipitation reaction to obtain a precursor material, wherein the mixed metal salt solution includes a formula amount of nickel ions, iron ions, manganese ions and M ions; The precursor material and the sodium source are mixed and calcined according to the formula amount to obtain the core.
8. The preparation method according to claim 7, characterized in that: Under a protective atmosphere, carrying out the coprecipitation reaction; Preferably, the temperature of the coprecipitation reaction is 20°C to 70°C, and the pH value is 8 to 12; Preferably, the calcination temperature is 800°C to 1400°C, and the calcination time is 10h to 25h; Preferably, the calcination is carried out in an oxygen atmosphere.
9. The preparation method according to any one of claims 4 to 8, characterized in that: When the core, the sodium iron phosphate pyrophosphate precursor material and the sodium source are mixed, a carbon source is also added; Preferably, the mass ratio of the core, the sodium iron phosphate pyrophosphate precursor material, the sodium source and the carbon source is (25-55):(25-55):(15-25):1; Preferably, the sintering is carried out in a protective gas; Preferably, the sintering temperature is 600° C. to 800° C., and the sintering time is 6 h to 12 h.
10. A sodium ion battery, characterized in that: The sodium ion battery comprises the doped and coated composite sodium positive electrode material as claimed in any one of claims 1 to 3.
Citation Information
Cited By
Composite polyanionic sodium battery positive electrode material as well as preparation method and application thereof
CN120664514A
Tungsten-doped composite positive electrode material, positive electrode plate, sodium ion battery and electric equipment
CN120998985A
A tungsten-doped composite positive electrode material, a positive electrode sheet, a sodium-ion battery and an electric device
CN120998985B
Positive electrode material, positive plate, sodium ion battery and electric equipment
CN120998986A
A positive electrode material, a positive electrode sheet, a sodium-ion battery and an electric device
CN120998986B